Analysis and design of low gas emission of ethanol fuel from ionic liquid-assisted pretreatment of biomass. Issue 1 (April 2021) - Utami, A R I; Sulaeman, M F; Mei, M
Abstract: The growth of gas emissions (GE) in the environment that stirred climate change, has correlated with the decline of fossil fuels. Generally, GE was produced by burning fossil fuels such as gasoline in the combustion engine. Gasoline has higher air toxic emissions than ethanol. Hence, the investigation of ethanol has gained attention. On the other hand, biomass has become a renewable source of ethanol. However, due to the rigid structure of biomass, biomass pretreatment is needed before the hydrolysis and fermentation process. Recently, growing attention has been devoted to applying ionic liquids (ILs)-assisted pretreatment despite the high-cost process. Therefore, in this study, to optimize the ethanol production from biomass, the simulation using SuperPro Designer (SPD) software was conducted. Bagasse as biomass material was treated by IL, namely choline acetate (ChOAc), with the range of ratio IL/biomass of 0–1.5. The developed SPD model was validated with published data. The results indicated that the minimum ratio of IL/biomass was 1.3. When in the hydrolysis performed at high-loading after 72 h reaction time, the glucose and xylose concentrations were 49 g/L and 13 g/L, respectively. When the fermentation process was conducted, the initial mixed sugar solution concentration was 23 g/L of glucose and 6 g/L of xylose. Then, the ethanol concentration was 15 g/L at 24 h, which was 89% of the theoretical ethanol yield. To conclude, the developed SPD model not only could support to optimize the biomass refinery into low GE of ethanol but also could reduce large cost experimental.